(untitled) (Research, Society and Development, 2023)
Nosocomial pneumonia is a respiratory tract infection acquired in the Intensive Care Unit (ICU), most often after the first 48 hours of the patient’s intubation. The dental surgeon includes from the moment he favors oral maintenance, where the patient is unable to perform basic tasks, such as daily oral hygiene. The fragility of patients undergoing hospitalization allows them to become more vulnerable to bacterial infections, causing complications that put their lives at risk. This literature review sought to show the importance of including the dentistry professional in the multidisciplinary team. The methodology of this work was carried out through research into scientific articles that prove the importance of implementing dental surgeons in ICUs, obtaining results that validate that prevention through oral hygiene in bedridden patients points to a significant disadvantage in the amount of cases that would possibly evolve into nosocomial pneumonia.